Konstruksi Berita Politainment Anggota DPR RI Mulan Jameela dan Krisdayanti di Media Online - Indah Suryawati (DIII Prodi Humas Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2020)
The success of fourteen artists to become members of the Indonesian Parliement 2019-2024 drew the attention of national media, including online media. However, some online media deliberately package this event in the form of politainment news. This is seen in the news about Mulan Jameela and Krisdayanti on Tribunnews.com and Detik.com. This research aims to find out the news construction of Mulan and Krisdayanti politainment news when officially appointed as a member of the Indonesian Parliament 2019-2024. The research method used is the Framing Zhongdang Pan and Gerald M. Kosicki. Pan Kosicki's framing device is divided into four large structures : syntactic structure, script structure, thematic structure, and rhetorical structure. The object of the research was the news texts Mulan and Krisdayanti as members of the Indonesian Parliament in Tribunnews.com and Detik.com in the October 2019 period. The results showed that the cognitive tools used by Tribunnews.com and Detik.com in coding information and interpreting events about Mulan and Krisdayanti as members of the Indonesian Parliament are constructed differently. The construction of Tribunnews.com and Detik.com tends to be more profitable for Krisdayanti than Mulan. The most highlighted side is the clothing choices used by Mulan and Krisdayanti, their relationship with each other's life partners to cases they have faced before. The success of Mulan and Krisdayanti in the Indonesian Parliement 2019-2024 was not so highlighted.